2017
DOI: 10.2217/pme-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

How Do Providers Discuss the Results of Pediatric Exome Sequencing with Families?

Abstract: Aim This study provides preliminary data on the process and content of returning results from exome sequencing offered to children through one of the Clinical Sequencing Exploratory Research (CSER) projects. Materials & methods We recorded 25 sessions where providers returned diagnostic and secondary sequencing results to families. Data interpretation utilized inductive thematic analysis. Results Typically, providers followed a results report and discussed diagnostic findings using technical genomic and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…As the level of complexity in genetic testing increases, new communicative competences may be needed to secure patients' engagement and understanding. The use of scientific jargon, technical terms, and level of details conveyed to patients may sometimes be too pronounced 28 . The focus on providing information may overshadow the equivalently important task of addressing values, hopes, and concerns 29 .…”
Section: Discussionmentioning
confidence: 99%
“…As the level of complexity in genetic testing increases, new communicative competences may be needed to secure patients' engagement and understanding. The use of scientific jargon, technical terms, and level of details conveyed to patients may sometimes be too pronounced 28 . The focus on providing information may overshadow the equivalently important task of addressing values, hopes, and concerns 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This study provides evidence for a unified view of intentions for approaching informed consent for exome sequencing, although additional research is needed to understand how these intentions translate into practice. Observations from a recent study of exome result return clearly demonstrated providers’ attempts to assess patient understanding, but found misunderstandings were not fully addressed and many of these sessions defaulted to information‐heavy communication (Walser et al, ). This work may be valuable to future research as a framework for assessing concordance between the stated priorities and content of actual consent sessions.…”
Section: Discussionmentioning
confidence: 99%
“…More experience with exome sequencing may also lead to increased comfort with discussions of uncertainty and provision of anticipatory guidance prior to results disclosure. As such, counselors can help patients to frame VUS results in a productive manner as they may represent possibilities for clarity and an opportunity for partnering with the care team (Walser et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details can be prioritized with information that patients are most interested in, such as management and next steps regarding their conditions. 28 Different forms of media such as videos and illustrations can be also utilized to make information easier to understand for diverse consumers. We propose that text readability could be improved in a scalable, automated fashion using NLP tools and public databases.…”
Section: Discussionmentioning
confidence: 99%